The Effect of Acupuncture Therapy with a Combination of Moxibustion in Cases of Low Back Pain on Changes in Pain Scale in Mekarjaya Village, Indramayu Regency - Rina, Asfarina Fajri; Eka Putri, Kurnia; Nugraha, Nurtama Aditya (Indonesian Journal of Acupuncture, 2025)
Low back pain is a musculoskeletal disorder caused by abnormalities or dysfunctions in the muscles and tendons, often triggered by excessive physical activity or work that demands high energy and muscle strength, thereby increasing the risk of musculoskeletal injury. This study aimed to determine the effect of acupuncture therapy combined with moxibustion on changes in pain scale among patients with low back pain in Mekarjaya Village, Indramayu Regency. Using a quasi-experimental design with two groups (pretest–posttest), 32 subjects were divided into an acupuncture-only group and an acupuncture plus moxibustion group. Pain intensity was measured using the Numeric Rating Scale (NRS) before and after the intervention, and data were analyzed using the Mann–Whitney and Wilcoxon tests. The results showed a significant decrease in NRS pain scores after the intervention in both groups (p < 0.050). The Mann–Whitney test revealed a significant difference between the two groups (p = 0.001), with the combination therapy group showing a greater reduction in pain than the acupuncture-only group. Thus, acupuncture therapy combined with moxibustion is more effective than acupuncture therapy alone in reducing low back pain and may serve as an effective complementary approach for managing this condition.